Interleukin-7 Unveils Pathogen-Specific T Cells by Enhancing Antigen-Recall Responses. (28th February 2018) - Terrazzini, Nadia; Mantegani, Paola; Kern, Florian; Fortis, Claudio; Mondino, Anna; Caserta, Stefano
Abstract : IL-7 supports host immunity in lymphopenic and immunosuppressed patients and expands tumor-reactive T cells for adoptive immunotherapy. Here, we report that IL-7 also enables the accumulation of clinically relevant pathogen-reactive T cells from TB-, CMV-, and Candida albicans -infected individuals. Abstract: Background: Interleukin (IL)-7 promotes the generation, expansion, and survival of memory T cells. Previous mouse and human studies showed that IL-7 can support immune cell reconstitution in lymphopenic conditions, expand tumor-reactive T cells for adoptive immunotherapy, and enhance effector cytokine expression by autoreactive T cells. Whether pathogen-reactive T cells also benefit from IL-7 exposure remains unknown. Methods: In this study, we investigated this issue in cultures of peripheral blood mononuclear cells (PBMCs) derived from patients infected with various endemic pathogens. After short-term exposure to IL-7, we measured PBMC responses to antigens derived from pathogens, such as Mycobacterium tuberculosis, Candida albicans, and cytomegalovirus, and to the superantigen Staphylococcus aureus enterotoxin B. Results: We found that IL-7 favored the expansion and, in some instances, the uncovering of pathogen-reactive CD4 T cells, by promoting pathogen-specific interferon-γ, IL-2, and tumor necrosis factor recall responses. Conclusions: Our findings indicate that IL-7 unveils and supports reactivation of pathogen-specific T cells with possible diagnostic, prognostic, and therapeutic significance of clinical value, especially in conditions of pathogen persistence and chronic infection.